Multiple colorectal adenomas in Lynch syndrome - Jain, Ayushi; Alimirah, Maryam; Hampel, Heather; Pearlman, Rachel; Ma, Jianing; Peng, Jing; Kalady, Matthew F.; Stanich, Peter P. (Frontiers in Oncology, 2022)
Background: Lynch syndrome has not traditionally been considered to have a high colorectal adenoma burden. However, with increasing adenoma detection rates in the general population, the incidence of adenoma detection in Lynch syndrome may also be increasing and leading to higher cumulative adenoma counts. Aim: To clarify the prevalence and clinical impact of multiple colorectal adenomas (MCRA) in Lynch syndrome. Methods: A retrospective review of patients with Lynch syndrome at our institution was performed to assess for MCRA (defined as ≥10 cumulative adenomas). Results: There were 222 patients with Lynch syndrome among whom 14 (6.3%) met MCRA criteria. These patients had increased incidence of advanced neoplasia (OR 10, 95% CI: 2.7-66.7). Conclusions: MCRA is not unusual in Lynch syndrome and is associated with a significantly increased likelihood of advanced colon neoplasia. Consideration should be given to differentiating colonoscopy intervals based on the presence of polyposis in Lynch syndrome.